Romania - A Risk Analysis and Screening Approach for Climate Change Mitigation and Adaptation Options : A Tool for Climate Action Planning - World Bank (Washington, DC, 2015)
The current report is a milestone for preparing the Romanian climate change (CC) action plan. A CC action plan should be based on the consolidation and coordination of both mitigation and adaptation measures and options. An important step in the elaboration of such a plan is the selection of appropriate actions. This selection requires the involvement of competent authorities in the key sectors, including, in the case of Romania, transport, energy, urban, water, agriculture, and forestry. The screening approaches are used to facilitate a transparent decision-making process in various fields such as environmental impacts, dangerous substances, environmental footprint of products, or CC actions. The report is structured as follows: section one gives introduction. Section two summarizes the usage of screening approaches in the field of CC and environment by different European Union (EU) member states and by the European Commission. Section three discusses the main categories of mitigation and adaption measures that can be included in a CC action plan. Section four presents the screening approach and process and describes several complementary tools (multi-criteria analysis, cost-benefit analysis (CBA), cost effectiveness analysis (CEA), modeling) that should be used when the screening approach is insufficient. Section five provides a conclusion and key recommendations.